Magnetically actuated tissue engineered scaffold: insights into mechanism of physical stimulation. Issue 6 (21st January 2016) - Sapir-Lekhovitser, Yulia; Rotenberg, Menahem Y.; Jopp, Juergen; Friedman, Gary; Polyak, Boris; Cohen, Smadar
Abstract : Magnetic alginate scaffolds exposed to a time-varying uniform magnetic field reversibly deform to generate bending ( F b )/stretching ( F s ) forces that may exert mechanical effects on cells. Abstract : Providing the right stimulatory conditions resulting in efficient tissue promoting microenvironment in vitro and in vivo is one of the ultimate goals in tissue development for regenerative medicine. It has been shown that in addition to molecular signals ( e.g. growth factors) physical cues are also required for generation of functional cell constructs. These cues are particularly relevant to engineering of biological tissues, within which mechanical stress activates mechano-sensitive receptors, initiating biochemical pathways which lead to the production of functionally mature tissue. Uniform magnetic fields coupled with magnetizable nanoparticles embedded within three dimensional (3D) scaffold structures remotely create transient physical forces that can be transferrable to cells present in close proximity to the nanoparticles. This study investigated the hypothesis that magnetically responsive alginate scaffold can undergo reversible shape deformation due to alignment of scaffold's walls in a uniform magnetic field. Using custom made Helmholtz coil setup adapted to an Atomic Force Microscope we monitored changes in matrix dimensions in situ as a function of applied magnetic field, concentration of magnetic particles within the scaffold wall structure and rigidity of the matrix. Our results show that magnetically responsive scaffolds exposed to an externally applied time-varying uniform magnetic field undergo a reversible shape deformation. This indicates on possibility of generating bending/stretching forces that may exert a mechanical effect on cells due to alternating pattern of scaffold wall alignment and relaxation. We suggest that the matrix structure deformation is produced by immobilized magnetic nanoparticles within the matrix walls resulting in a collective alignment of scaffold walls upon magnetization. The estimated mechanical force that can be imparted on cells grown on the scaffold wall at experimental conditions is in the order of 1 pN, which correlates well with reported threshold to induce mechanotransduction effects on cellular level. This work is our next step in understanding of how to accurately create proper stimulatory microenvironment for promotion of cellular organization to form mature tissue engineered constructs.